4-Aminopyridinium-3-sulfonate monohydrate - Zhu, Zhi Biao; Gao, Shan; Ng, Seik Weng (International Union of Crystallography, 2011)
The reaction of 4-aminopyridine and oleum yielded the title hydrated zwitterion, C5H6N2O3S·H 2O. There are two formula units in the asymmetric unit. The H and non-H atoms of both zwitterions lie on a mirror plane except for one sulfonate O atom. The water molecules are also situated on a mirror plane. In the crystal, the zwitterions and water molecules are linked by O -H⋯O and N -H⋯O hydrogen bonds, generating a threedimensional network.